Impacto do uso dos serviços odontológicos na dor dentária de acordo com a cor da pele de adolescentes: uma coorte de 10 anos - Rauber, Everton Daniel (2022)
Studies on the oral health of the population have paid special attention to sociodemographic variables, such as self-reported race, as well as data referring to the habits or behaviors of individuals in relation to their oral health, which can impact clinical and subjective outcomes, such as the occurrence of dental pain. Among the existing types of orofacial pain, those of dental origin have been reported as the most frequent and can affect social interaction, daily activities and negatively impact the individual's quality of life, whether adult or child. However, the study of dental pain as an outcome is still little explored and, being a variable responsible for already proven diseases, it is important to clarify possible factors that generate an impact on its occurrence. Therefore, the objective of the study was to evaluate the effect of the interaction between the use of dental services and the skin colour reported by parents on the occurrence of dental pain over time, in view of the literature on the differences found in the care of self- reported individuals whites and non-whites. This study is a cohort with 10 years of follow-up, started in 2010 with a representative sample of 639 preschool children (1 to 5 years old) evaluated in the city of Santa Maria, southern Brazil. Subsequently, the individuals were reassessed in the years 2017 and 2020. The use of dental services, race and the presence of dental pain were self-reported by the individuals, and the predictors were collected from the WHO and IBGE criteria, respectively, and the outcome from a direct question already used in other studies. Multilevel logistic regression analysis was performed to assess the interaction between skin colour and use of dental services in the occurrence of dental pain over time. Results are presented as Odds Ratio (OR) and 95% confidence interval (95%CI). About 449 and 429 were reassessed in 2017 and 2020, generating response rates of 70.3% and 67.1%, respectively. The occurrence of toothache across the cohort was 60.7%. Caucasian individuals who used dental services throughout the cohort had a 51% lower chance of having a toothache than those who used dental services but were non-white (OR 0.49; 95% IC 0.27-0.90). It was concluded that there was racial inequity in the occurrence of toothache among individuals who managed to make use of dental services throughout the follow-ups.